2019
DOI: 10.1002/cam4.2440
|View full text |Cite
|
Sign up to set email alerts
|

HOXA10 induces BCL2 expression, inhibits apoptosis, and promotes cell proliferation in gastric cancer

Abstract: Homeobox A10 (HOXA10) has been implicated critical for the promotion of carcinogenesis, but the underlying mechanism between HOXA10 and malignant gastric cancer (GC) phenotype remains elusive. In the present study, we analyzed and validated that HOXA10 and BCL2 expressions were elevated both at the mRNA and protein levels in GC tissues. Upregulated HOXA10 promoted GC cell proliferation with reduced apoptosis in vitro and accelerated GC tumor growth in vivo. Bioinformatics analysis and quantitative real‐time po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Decreased expression of HOXA10 accelerated the acetylation of p53 (Lys382) and suppressed the transcription of histone deacetylase 1 (HDAC1; a potential deacetylase for p53) to activate p53 transcription (26). Additionally, HOXA10 might promote cell proliferation by elevating Bcl-2 expression and inhibiting apoptosis in gastric cancer, and high expression of HOXA10 predicted poor overall survival in gastric cancer patients (27). In this study, we found high expression of HOXA10 in LSCC tissues.…”
Section: Discussionmentioning
confidence: 64%
“…Decreased expression of HOXA10 accelerated the acetylation of p53 (Lys382) and suppressed the transcription of histone deacetylase 1 (HDAC1; a potential deacetylase for p53) to activate p53 transcription (26). Additionally, HOXA10 might promote cell proliferation by elevating Bcl-2 expression and inhibiting apoptosis in gastric cancer, and high expression of HOXA10 predicted poor overall survival in gastric cancer patients (27). In this study, we found high expression of HOXA10 in LSCC tissues.…”
Section: Discussionmentioning
confidence: 64%
“…We have also identified previous research that supports their importance in cancer. High expression of HOXA10 can promote tumor development in gastric cancer, hepatocellular carcinoma, and ovarian cancer [19][20][21]. More importantly, downregulated LINC00483 suppresses tumor cell invasion, migration, and epithelial to mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…OCT-4 is a homeobox gene well known for its function in generating induced pluripotent stem cells (Bhartiya, 2013;Seiler et al, 2011); this gene has also been identified as an oncogene known for promoting the features of cancer stem cells (Li et al, 2017;Phiboonchaiyanan & Chanvorachote, 2017). In addition to OCT-4, an increasing body of evidence reveals that homeobox genes may participate in the promotion of various malignant phenotypes such as the proliferation, migration and invasion of cancers (Hirao et al, 2019;Miwa & Kanda, 2019;Rodini et al, 2012;Song et al, 2019). We have previously reported that HoxC6, another member of homeobox superfamily, functions as an oncogene in ESCC (Tang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%